Xanthophore Distribution of Nemo (Amphiprion ocellaris) Skin Based on various Concentrations of Carotenoid Sources - Rini Pratiwi; Muhammad Yusri Karim; Dody Dh Trijuno (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract